Degradation by brown rot fungi increases the hygroscopicity of heat-treated wood - Belt, Tiina; Altgen, Michael; Awais, Muhammad; Nopens, Martin; Rautkari, Lauri (Elsevier, 2024)
Heat treatment increases the decay resistance of wood by decreasing its hygroscopicity, but the wood material remains degradable by fungi. This study investigated the degradation of heat-treated wood by brown rot fungi, with the aim of identifying fungal-induced hygroscopicity changes that facilitate degradation. Scots pine sapwood samples were modified under superheated steam at 200 and 230 °C and then exposed to Coniophora puteana and Rhodonia placenta in a stacked-sample decay test to produce samples in different stages of decay. Sorption isotherms were measured starting in desorption from the undried, decaying state to investigate their hygroscopic properties. Although there were substantial differences in degradative ability between the two fungi, the results revealed that decay by both species increased the hygroscopicity of wood in the decaying state, particularly at high relative humidity. The effect was stronger in the heat-treated samples, which showed a steep increase in moisture content at low decay mass losses. The reference samples showed decreased hygroscopicity in absorption from the dry state, while the heat-treated samples still showed an increase at low mass losses. Near infrared spectroscopy showed that the early stages of decay were characterised by the degradation of hemicellulose and chemical changes to cellulose and lignin, which may explain the increase in hygroscopicity. The results provide a new perspective on brown rot decay and offer insight into the degradation of heat-treated wood.
Keywords: Durability; Dynamic vapor sorption; Thermal modification; Wood decay